A Voice and a Vote: The Advisory Board Experiences of Spanish-Speaking Latina Mothers - DeCamp, Lisa Ross (Hisp Health Care Int, 2015)
Latino children experience disparities in health care access and quality. Family advisory groups for clinics and hospitals may be one way to address disparities. We implemented and sustained an advisory board whose parent participants were exclusively limited-English proficient Latina mothers. As part of the board evaluation, we conducted semistructured individual interviews with parent participants during initial participation and after the final board meeting of the year. Members were satisfied with their board participation in both initial and follow-up interviews. They reported that board membership was an important way to improve clinic services and a unique opportunity for Latinos in the community. Experiences of discrimination and marginalization in health care settings were a theme across interviews. Members reported board membership countered these negative experiences. An advisory board including Spanish-speaking parents is an opportunity to engage vulnerable populations, which may result in broader impact on health care disparities. Los niños latinos experimentan disparidad en el acceso y calidad del cuidado de salud. Grupos de familias asesoras para clínicas y hospitales pueden ser una forma de hacer frente a las disparidades. Nosotros implementamos y sostuvimos un consejo asesor cuyos participantes fueron exclusivamente madres latinas con dominio limitado del inglés. Como parte de la evaluación del consejo, condujimos entrevistas semi-estructuradas individuales con las madres participantes durante la participación inicial y después de la última reunión del año del consejo. Los miembros estaban satisfechas con su participación en el consejo en ambas entrevistas, la inicial y la de seguimiento. Ellas reportaron que ser miembros del consejo era una forma importante para mejorar los servicios de la clínica y una oportunidad única para los latinos en la comunidad. Las experiencias de discriminación y marginalización en las instalaciones de cuidado de salud eran un tema a lo largo de las entrevistas. Los miembros reportaron que ser miembros del consejo contrarrestó estas experiencias negativas. Un consejo asesor incluyendo padres que hablan español es una oportunidad para involucrar a poblaciones vulnerables, las cuales pueden resultar en un impacto más amplio en las disparidades del cuidado de salud.